1947
DOI: 10.1098/rstb.1947.0001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations of the shoot apex of Dryopteris aristata Druce

Abstract: A method whereby the apical meristem of the fern Dryopteris aristata Druce can be partially isolated from the adjacent lateral organs and tissues is described. This procedure has been adopted as a means of investigating growth and morphogenesis at the shoot apex. The technique involves the severance of the incipient vascular tissue which originates immediately below the apical meristem; the isolated meristem is thus seated on a plug of growing medullary parenchyma. Leaf primordia can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1949
1949
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…Similar results were obtained from experimental analyses that investigated the integration of the meristem in angiosperms and ferns. When the meristem of either Impatiens (angiosperm) or Dryopteris (fern) was punctured, more than two apices were formed (Wardlaw, 1949;Steeves & Sussex, 1989). These results suggest that both fern and seed plant meristems are multicellular and there is communication among the cells of the meristem.…”
Section: Introductionmentioning
confidence: 59%
“…Similar results were obtained from experimental analyses that investigated the integration of the meristem in angiosperms and ferns. When the meristem of either Impatiens (angiosperm) or Dryopteris (fern) was punctured, more than two apices were formed (Wardlaw, 1949;Steeves & Sussex, 1989). These results suggest that both fern and seed plant meristems are multicellular and there is communication among the cells of the meristem.…”
Section: Introductionmentioning
confidence: 59%
“…Also when the leaves were removed the leaf stumps did not bleed so much as to obscure the apex, and the plant had been used very often by other workers (e.g. Ball (1949); Snow & Snow, 1931, 1947, so that their results could be compared with any from this investigation and used if needed. It was found that the lupin apex was very robust, and few of the apices died after the operations.…”
Section: ) Materials and Methodsmentioning
confidence: 99%
“…Some of the most interesting experimental work was being carried out by Claude W. Wardlaw, Professor of cryptogamic botany at the University of Manchester, UK. Wardlaw had followed up on the work of the Snows and performed a series of ingenious experiments on the shoot apex of ferns (Wardlaw, 1947). He became supervisor to the 22-year-old PhD student from New Zealand.…”
Section: Introductionmentioning
confidence: 99%